EDUKASI DAN KAMPANYE PENCEGAHAN PENYAKIT MENULAR (HIV-AIDS DAN TBC) DI TEMPAT KERJA - Herdianti, Herdianti; Oktarizal, Hengky; Martha, Elsusi; Sembiring, Firdaus Yustisia; Dinilhaq, Fauzal (ASOSIASI IDEBAHASA KEPRI, 2025)
HIV-AIDS and Tuberculosis (TB) are major health problems still faced by workers, especially in the industrial, construction, and migrant sectors. Lack of awareness, social stigma, and limited access to health information and services are major obstacles. Therefore, an effective educational approach and campaign are needed to raise awareness and shape preventive behavior in the work environment. This community service program aimed to improve workers' knowledge and attitudes regarding the prevention of HIV-AIDS and TB at PT X in Batam City. The method of implementing the activity includes initial observation, literature study, concept planning, implementation of education, focus group discussions (FGD), and evaluation through pre-post tests. The target of the activity is 30 PT X workers. Knowledge and attitudes are measured using a structured questionnaire, then the changes are analyzed after the educational intervention. Through educational sessions, group discussions, and visual campaigns, pre- and post-tests were conducted to evaluate the impact. The results showed significant improvement in knowledge (average score increased from 58.2 to 78.7) and positive attitudes (from 33% to 83%). This program proved effective in fostering preventive behaviors and reducing stigma against HIV and TB patients in the workplace. It is hoped that companies can continue these efforts sustainably through supportive policies, screening facilities, and regular counseling.